2014
DOI: 10.1186/1472-6963-14-237
|View full text |Cite
|
Sign up to set email alerts
|

Health-service performance of TB treatment for indigenous and non-indigenous populations in Brazil: a cross-sectional study

Abstract: BackgroundHealth-service evaluation studies are fundamental for proposing interventions and ensuring improvements in healthcare quality. The present study assesses the performance of health services for indigenous and non-indigenous populations with regard to tuberculosis (TB) control.MethodsInterviews with TB patients who underwent treatment between 2009 and 2011 were conducted using the Primary Care Assessment Tool adapted for TB care in Brazil.ResultsPrimary healthcare (PHC) was the first treatment for most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…It is always challenging for anyone to provide daily DOT to patients for over 20 months. Poor implementation of DOT has been reported in many studies, though healthcare providers may be the named DOT providers [ 57 , 58 ]. Studies found that family members, with more time to spend with the patients with caring minds, were more cost-effective in terms of time and resources compared to healthcare providers [ 59 ], and may improve MDR-TB treatment outcomes [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is always challenging for anyone to provide daily DOT to patients for over 20 months. Poor implementation of DOT has been reported in many studies, though healthcare providers may be the named DOT providers [ 57 , 58 ]. Studies found that family members, with more time to spend with the patients with caring minds, were more cost-effective in terms of time and resources compared to healthcare providers [ 59 ], and may improve MDR-TB treatment outcomes [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A quarter of the respondents mentioned having needed to return to the Casais five times, and waiting for more than 30 days to get conclusive diagnosis, similarly to reports from rural areas in India and from interior regions of Brazil. [24][25][26][27] Traditional indigenous medicine appeared among the treatment options, but without excluding biomedicine. Both use of medicinal plants and prayer and/or shamanism, either on their own or in association with use of Western medicine, were considered in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the high incidence of tuberculosis in the Brazilian indigenous population may be related to certain characteristics of those individuals, namely, difficult access to health services, inappropriate housing conditions with poor ventilation and high concentration of people in a single residence, illiteracy, high malnutrition rates, intestinal parasitic diseases, alcoholism, as well as immunological particularities ( 38 ) . Additionally, in the group of indigenous patients there are linguistic and cultural barriers which make the treatment more difficult ( 39 ) . These people live in villages, with poor conviviality with non-indigenous people.…”
Section: Discussionmentioning
confidence: 99%